Hubungan Pemanfaatan Buku Kesehatan Ibu dan Anak (KIA) dengan Pengetahuan Ibu tentang Stimulasi Tumbuh Kembang Anak Usia 0-24 Bulan - Desak Made Sri Mahayu; Ni Wayan Manik Parwati; Putu Ayu Ratna Darmayanti (Universitas Malahayati Lampung, 2026)
ABSTRACT The Mother and Child Health Handbook (KIA) serves as a medium for communication, information, and education to support maternal and child health services. The use of the KIA Handbook is believed to increase mothers' knowledge in caring for and stimulating the growth and development of children aged 0-24 months, however its use remains limited, especially in terms of conceptual information. This study aimed to find out the correlation between the use of the KIA Book and mothers' knowledge about stimulating the growth and development of children aged 0-24 months. A cross-sectional study design was employed with 289 respondents selected through convenience sampling. Data were collected through questionnaires assessing the level of utilization of the KIA Book and mothers' knowledge, then analyzed using Spearman Rank correlation test with a significance level of 0.05. The results showed that the median score for the utilization of the KIA Book was 17, and the median score for maternal knowledge was 16. Further statistical analysis indicated a strong correlation between the two variables (p-value 0.001 and p= 0.628). There is a strong correlation between the use of the KIA Book and maternal knowledge. The more optimal the KIA Book is use, the higher the mother's knowledge about the child's growth and developmental stimulation. Health workers, especially midwives, are expected to be more proactive in providing education and counselling to mothers, thus can fully utilize the KIA Book. Keywords: KIA Book, Stimulation, Growth, Development. ABSTRAK Buku Kesehatan Ibu dan Anak (KIA) berfungsi sebagai media komunikasi, informasi, dan edukasi untuk mendukung pelayanan kesehatan ibu dan anak. Pemanfaatan Buku KIA diyakini dapat meningkatkan pengetahuan ibu dalam merawat serta menstimulasi tumbuh kembang anak usia 0–24 bulan, namun penggunaannya masih terbatas, terutama pada bagian informasi konseptual. Penelitian ini bertujuan untuk mengetahui hubungan antara pemanfaatan Buku KIA dengan pengetahuan ibu mengenai stimulasi tumbuh kembang anak usia 0–24 bulan. Desain penelitian yang digunakan adalah cross-sectional dengan 289 responden. Data dikumpulkan melalui kuesioner yang menilai tingkat pemanfaatan Buku KIA dan pengetahuan ibu, kemudian dianalisis menggunakan uji korelasi Spearman Rank dengan tingkat signifikansi 0,05. Hasil menunjukkan median skor pemanfaatan Buku KIA sebesar 17 dan median skor pengetahuan ibu sebesar 16. Diperoleh nilai p 0,001 dan koefisien korelasi (ρ) = 0,628, yang menunjukkan hubungan kuat antara kedua variabel. Tidak ada hubungan antara pengetahuan dengan motivasi ibu hamil melaksanakan triple eliminasi untuk menurunkan kejadian penularan penyakit dari ibu ke anak di UPTD Puskesmas Mengwi II. Diharapkan tenaga kesehatan selalu menginformasikan kepada ibu hamil terkait pemeriksaan triple eliminasi. Kata Kunci: Buku KIA, Stimulasi, Tumbuh Kembang.